The process of forming integrated business structures using methods and technologies - Piletska, S.; Miahkykh, I. (Економічний вісник Донбасу, 2024)
This article presents an analysis of the conditions that facilitate the development of integration processes, methods and technologies for the formation of integrated business structures. In addition, it considers the advantages and disadvantages associated with these processes, methods and technologies. The analysis is centred on structural changes in the economy and forms of integrated business structures, which require a comparative analysis across different paradigms and concepts of integration. This enables the critical incentives for integration procedures to be identified and the contribution of integration processes to improving the efficiency of the business activities of integrated entities to be evaluated. The orientation of the organisational structure of integrated business entities facilitates the coordination of numerous independent activity systems, ensuring the regular reproduction of forms and the organisation of process interaction. Concurrently, the emphasis on co-organisation technologies helps resolve issues related to the management of the integration process. У статті аналізуються умови розвитку інтеграційних процесів, методи та технології формування інтегрованих бізнес-структур, а також їхні переваги й недоліки. Основна увага приділяється структурним змінам в економіці та формам побудови інтегрованих бізнес-структур, які вимагають порівняльного аналізу в різних парадигмах і концепціях інтеграції. Це допомагає визначити основні стимули інтеграційних процедур і оцінити внесок інтеграційних процесів у підвищення ефективності бізнес-діяльності об'єктів, що інтегруються. Орієнтація організаційної структури інтегрованих бізнес-структур сприяє координації багатьох незалежних систем діяльності, забезпечуючи регулярне відтворення форм і організації взаємодії процесів. Водночас акцент на технології співорганізації допомагає вирішити питання управління інтеграційним процесом.